The 58,000-dalton cellular inhibitor of the interferon-induced double-stranded RNA-activated protein kinase (PKR) is a member of the tetratricopeptide repeat family of proteins. - Lee, T G (1994)
PKR is a serine/threonine protein kinase induced by interferon treatment and activated by double-stranded RNAs. As a result of activation, PKR becomes autophosphorylated and catalyzes phosphorylation of the alpha subunit of protein synthesis eukaryotic initiation factor 2 (eIF-2). While studying the regulation of PKR in virus-infected cells, we found that a cellular 58-kDa protein (P58) was recruited by influenza virus to downregulate PKR and thus avoid the kinase's deleterious effects on viral protein synthesis and replication. We now report on the cloning, sequencing, expression, and structural analysis of the P58 PKR inhibitor, a 504-amino-acid hydrophilic protein. P58, expressed as a histidine fusion protein in Escherichia coli, blocked both the autophosphorylation of PKR and phosphorylation of the alpha subunit of eIF-2. Western blot (immunoblot) analysis showed that P58 is present not only in bovine cells but also in human, monkey, and mouse cells, suggesting the protein is highly conserved. Computer analysis revealed that P58 contains regions of homology to the DnaJ family of proteins and a much lesser degree of similarity to the PKR natural substrate, eIF-2 alpha. Finally, P58 contains nine tandemly arranged 34-amino-acid repeats, demonstrating that the PKR inhibitor is a member of the tetratricopeptide repeat family of proteins, the only member identified thus far with a known biochemical function.